Effectiveness of Kopiko Candy Product Placement Strategy in Korean Drama Doctor Slump: The Role of Product Involvement, Placement Prominence and Celebrity Endorsement - Syarifudin, Sailina Karimah; Rafiah, Kurnia Khafidhatur Rafiah Khafidhatur; Ihsan, Mochamad Chairul (Fakultas Ekonomi Universitas Garut, 2024)
The product placement strategy is increasingly favored in global marketing, especially through Korean drama streaming services, which are typically produced in series format. Kopiko candy leverages the popularity of Korean dramas by employing product placement in the Korean drama Doctor Slump. This study aims to examine the influence of product involvement, placement prominence, and celebrity endorsement on brand memory and brand attitude. The research involved 157 respondents who are fans of Korean dramas residing in Indonesia, aged 18 and above, who have watched the Doctor Slump series from episodes 1-16 and are aware of the presence of Kopiko candy in the scenes of the drama. The results of this study indicate a positive and significant relationship between the variables of product involvement, placement prominence, and celebrity endorsement on brand memory. Additionally, product involvement and celebrity endorsement also have a positive and significant effect on brand attitude.